The Effect of Photovoice on Speaking Skills at the Secondary School Level - Hidayat, Rifqi Aziz; Rofiudin, Rofiudin; Sulistianingsih, Endang (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2019)
The students need to be fluent in speaking to express their ideas and what they think in their minds also to communicate with others. As a matter of fact, speaking using Bahasa is not a big deal for students since it is their mother tongue, but as they have to speak in English, it becomes a big problem. Â They canâ€™t imagine what they want to speak, they are afraid and unconfident if they try to speak English. Therefore the teacher should provide the students' motivation to speak up and use the appropriate method in teaching speaking. Photovoice is a suitable method using a camera for supporting the process of teaching-learning. The purpose of the study is to identify the effect of using Photovoice on speaking skills at the secondary school level. We used a speaking test to complete and process the data. The participants of the study were the students at the secondary level. The outcome of the study revealed that the students who taught using Photovoice had better skills in speaking English than the students who were not taught using Photovoice. Through this method, the students become interested and active during the study. They seemed to enjoy and excited about an exhibition or presentation.